Tubularised incised plate hypospadias repair: a multicellular experience - Shahid, Shah Md. Ahsan; Rahman, Md. Mostafizur (KYAMC Journal, 2013)
Objectives: To report the outcomes in a series using modified tubularized incised plate (TIP) urethroplasty (Snodgrass) technique. The use of the TIP urethroplasty (Snodgrass) technique has gained wide acceptance among pediatric urologists for the correction of hypospadias repair because of its good cosmesis, low complication rate, and reliability in creating a vertically oriented meatus. Methods: A total of 54 boys aged 2 -13 years admitted in paediatric surgery ward Glanular(5.5%),Coronal(18.5%),Subcoronal(35.18%), Distal RMCH and IBH,Rajshahi with penile(11.1%),midpenile(9.6%) hypospadias underwent one-stage repair using a modified TIP repair during January,2010 to December,2010 were included in the study. Outcome was reviewed for each patient to determine the complications, reoperations, cosmesis, and functional results after surgery. Results: With at least 6 months of follow-up, all patients had achieved excellent functional and cosmetic results, with the meatus at the tip of the penis on follow-up. Three repairs for meatal stenosis and two for fistula were needed. Conclusions: The modified TIP procedure is a safe and reliable technique. It provides excellent cosmesis with a low reoperation rate. DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13317 KYAMC Journal Vol.1(2) January 2011,64-69